2019
DOI: 10.4049/jimmunol.1900084
|View full text |Cite
|
Sign up to set email alerts
|

Thymus-Derived Regulatory T Cells Exhibit Foxp3 Epigenetic Modification and Phenotype Attenuation after Mating in Mice

Abstract: Regulatory T cells (Tregs) are essential for maternal tolerance in allogeneic pregnancy. In preeclampsia, Tregs are fewer and display aberrant phenotypes, particularly in the thymic Treg (tTreg) compartment, potentially because of insufficient priming to male partner alloantigens before conception. To investigate how tTregs as well as peripheral Tregs (pTregs) respond to male partner seminal fluid, Foxp3 + CD4 + Tregs were examined in the uterus and uterus-draining lymph nodes in virgin estrus mice and 3.5 d p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 100 publications
1
27
0
Order By: Relevance
“…Despite this decrease, however, these authors found increased proliferative activity of RTE-tT Regs with superior suppressive activity compared to more mature T Reg cells. Consistent with this idea, in mice, tT Reg cells as defined by Nrp1 expression and demethylated status of the CNS2, proliferate in the uterusdraining para-aortic LNs as early as GD3.5 (59). The presence of organ-specific antigens can trigger local expansion of organspecific T Reg cells in draining LNs with considerable inter-organ differences in TCR usage by T Reg (16).…”
Section: Could Tolerance To the Fetus Be Driven By Tt Reg Cells In Prmentioning
confidence: 71%
See 2 more Smart Citations
“…Despite this decrease, however, these authors found increased proliferative activity of RTE-tT Regs with superior suppressive activity compared to more mature T Reg cells. Consistent with this idea, in mice, tT Reg cells as defined by Nrp1 expression and demethylated status of the CNS2, proliferate in the uterusdraining para-aortic LNs as early as GD3.5 (59). The presence of organ-specific antigens can trigger local expansion of organspecific T Reg cells in draining LNs with considerable inter-organ differences in TCR usage by T Reg (16).…”
Section: Could Tolerance To the Fetus Be Driven By Tt Reg Cells In Prmentioning
confidence: 71%
“…Nrp1 functions to increase sensitivity of T Reg to antigen and permit prolonged interaction with immature dendritic cells ( 57 ). Further, its expression is associated with prolonged survival of allogeneic grafts in mice ( 58 ) as well as demethylation at the CNS2 region of the Foxp3 locus ( 59 ), which is characteristic of tT Regs . On the other hand, 90% of CD4+CD8+ DP cells in the thymus are Nrp1+ ( 60 ) and can also be induced in conventional CD4+ T cells in vitro ( 58 ).…”
Section: Identification Of Ptreg and Tt Regmentioning
confidence: 99%
See 1 more Smart Citation
“…1F). Thymic Treg (tTreg) cells and peripheral Treg (pTreg) cells, distinguished on the basis of NRP1 expression (Yadav, et al, 2012), both contribute to the Treg increase in early pregnancy (Moldenhauer, et al, 2019). Both tTreg and pTreg cells in the PALN failed to increase after prednisolone treatment (Fig.…”
Section: Prednisolone Reduces Cd4 + T Cells In Early and Mid-gestation Pregnancymentioning
confidence: 99%
“…Implantation only occurs if immune cells in the uterine endometrium exhibit a favourable, permissive response. In particular, expansion and recruitment of specialized immune cells known as regulatory T cells (Treg cells) must occur (95)(96)(97)(98). Treg cells interact with dendritic cells and macrophages to promote decidualisation of uterine stromal cells, suppress inflammation, and inhibit effector immunity towards fetal antigens.…”
Section: Immune Mechanisms Essential For Implantation and Placental Developmentmentioning
confidence: 99%